(1239) Optimal and approximate ordering in solving inventory problems الترتيب الأمثل والتقريبي في حل مشاكل المخزون - Hamza, Abdel-Kader (The Institute Of National Planning., 2018)
Since the development of the original lot- size inventory model in 1915. many researches was done analysis mathematical models for describing ordering policies for one or more products invariably. it was assumed implicitly that once units enter in to inventory, they (live) for ever or else they expire after only a single planning period.